Lithology Classification and Porosity Estimation of Tight Gas Reservoirs With Well Logs Based on an Equivalent Multi-Component Model - Wang, Zhenyang; Nie, Xin; Zhang, Chong; Wang, Mingrui; Zhao, Junwei; Jin, Longde (Frontiers in Earth Science, 2022)
Tight gas makes up a significant portion of the natural gas resources. There develop tight gas reservoirs with great reserve and economic potential in the west Sichuan Basin, China. Due to the complex mineral component and heterogeneity of the thick tight sand formations, the reservoir parameters are challenging to evaluate from well logs using conventional methods, even the fundamental porosity. The mineral components must be considered. In this study, based on the analysis of different logging responses of varying lithology, we introduced the complex reservoir analysis (CRA) method. CRA is always used in the carbonate reservoirs to calculate the different rock component volume fractions and can be used to classify the lithology and calculate the porosity simultaneously. By analyzing the component, a new equivalent component method (CRAE) is proposed based on the CRA method in this paper. In this method, the AC-CNL equation calculated porosity is calibrated according to the core porosity data to set the rock components’ parameters. After calibration, the rock component fractions and porosity can be calculated accurately. And according to the relationship between the grain size and natural gamma-ray, a granularity median model was established. Six lithology types, including coarse-grained quartz sandstone and coarse-grained lithic sandstone, etc., are distinguished, and the porosity is estimated in the study area. The identification results are compared with the mud logging data and other methods. It shows that this method is very well adequate in those tight sandstone gas reservoirs in the study area.